Nuclear governmentality: Governing nuclear security and radiation risk in post-Fukushima Japan. (December 2019) - Nadesan, Majia Holmer
Nuclear governmentality is offered as a conceptual contribution to research on energy politics, security studies, and nuclearity. Nuclear governmentality is conceived as a logic of government in the Foucauldian sense, that describes contiguities in conduct and symbolic representations found across disparate dispositifs, especially (albeit not exclusively) those strategically aimed at eliciting and exploiting atomic forces in medicine, industry, and war. This project demonstrates the logic and technologies of power specific to nuclear governmentality in post-Fukushima Daiichi energy commitments, evacuation policies, risk assessments, and health surveillance programs. Nuclear governmentality is at once modern in its adaptation of regimes of risk management and anachronistic in its prioritization of sovereign decisionality in their developments and deployments, especially evident in the legal principle of the minimum standard and the instrument of the permissible dose.